Japanese language learning with social media (Journal of Oriental Studies, 2016)
The  learninghas steadily grown over the last 5 years since the appearance of sites Busuu, Italki, livemocha, Voxswap etc. This article focuses on the use of one such site, called Lang-8, and the ways learners of Japanese as a foreign language construct their own learning environment, by managing their online identities to form cooperative language learning opportunities.
Keywords: social sites; group; task; social constructivist.